MUTU DAN KONDISI MIKROBIOLOGIS PENGOLAHAN TERASI UDANG SKALA UKM DI SENTRA PRODUKSI CIREBON - Suniyyah Azmi; Rusky Intan Pratama; Radestya Triwibowo; Lantun Paradhita Dewanti; Iss Rostini (Jurnal Perikanan Unram, 2024)
Terasi is a fermented product made from fish or shrimp, that undergoes a salting process. The small-medium scale of shrimp paste industry are widespread in Indonesia, particularly in the Cirebon area. Traditional processing of shrimp paste involves natural or spontaneous fermentation processes, which involves microbes from the surrounding environment that can grow and contaminate the shrimp paste. This study aims to analyze the microbiological conditions and quality of traditional shrimp paste produced in Cirebon production centers based on SNI 2716: 2016 for shrimp paste. The survey method used purposive sampling based on specific criteria to determine sample points. The observation parameters tested included pathogenic bacteria E.coli (presumptive) using the petrifilm method (3MTM), Salmonella sp. and Vibrio parahaemolyticus using the PCR method, total mold using the ALT (Total Plate Number) method, aw, pH, and proximate. The overall data was analyzed using quantitative descriptive analysis. The results showed that E.Coli counts ranging from 6.00 x 102 to 2.10 x 104 CFU/g, thus not meeting SNI 2716: 2016 standard for shrimp paste. However, the final product did not show contamination by Salmonella sp, and Vibrio parahaemolyticus. The total mold contamination in the final shrimp paste product from processor A (Desa Jatimerta) and B (Desa Panjunan) ranged from 1.80 x 10² to 4.30 x 10³ CFU/g. The chemical analysist result of the final products from both processor generally met the SNI 2716: 2016 standards, except for processor B’s samples, where the water and ash content did not meet the standards. Key words: Fermentation, Molecular Identification, Contamination, Pathogen, Shrimp Paste